Pendampingan Membangun Brand Image Lembaga Pendidikan di SMK Mambaul Ulum Paiton - Muhammad Ainul Yaqin; Muhammad Deni Santoso; Muhammad Fahim (Interaksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program aims to assist and provide an understanding of branding strategies implemented to enhance the school's competitiveness. Branding is crucial in addressing global competition, as educational institutions must carefully improve their quality and identify opportunities within the community by establishing a positive brand image in the public eye.The program is conducted using a qualitative case study approach. It is carried out at SMK Mambaul Ulum Paiton, Probolinggo, with the goal of improving the school's professional quality specifically and its societal value more broadly.Based on the assistance provided, SMK Mambaul Ulum Paiton, Probolinggo, introduces its distinctive characteristics and strengths through branding efforts in print media, online platforms such as websites, and social media. Additionally, to strengthen its brand image, SMK Mambaul Ulum strives to prove its quality through graduates who are job-ready.